Phthalate Exposure and Long-Term Epigenomic Consequences: A Review - Dutta, Sudipta; Haggerty, Diana K.; Rappolee, Daniel A.; Ruden, Douglas M. (Frontiers in Genetics, 2020)
Phthalates are esters of phthalic acid widely used as plasticizers to soften and increase the flexibility in polyvinyl chloride (PVC) plastics. They are also used in cosmetics and other daily personal care products. Phthalates are not covalently bound to plastics and easily leach into the environment and enter the human body by dermal absorption, ingestion or inhalation. Several in vitro and in vivo studies suggest that phthalates can act as endocrine disruptors and cause moderate reproductive and developmental toxicities. Furthermore, phthalates can cross the placental barrier and affect the developing fetus. Thus, phthalates are ubiquitous food and environmental contaminants with potential adverse health effects in humans. This review focusses on studies conducted in the field of toxicogenomics of phthalates and discusses possible transgenerational and multigenerational effects caused by phthalate exposure during any point of the life-cycle.